KOMPETENSI KEWIRAUSAHAAN KEPALA SEKOLAH PADA SEKOLAH MENENGAH PERTAMA NEGERI DI KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - Reni Oktavia (Universitas Negeri Padang, 2014)
The goal of this research are to see information about the enterpreneurship competency of headmasters. The population is 76 teachers and the sample is 76 people because this research is total sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level . The result of this research are the enterpreneur competency of headmasters in SMP Negeri di Kecamatan Hiliran Gumanti Kabupaten Solok stay in good enough category. Key word : enterpreneurship competency of headmasters